2016
DOI: 10.2147/dddt.s118145
|View full text |Cite
|
Sign up to set email alerts
|

Increased localized delivery of piroxicam by cationic nanoparticles after intra-articular injection

Abstract: Piroxicam (PRX), a potent nonsteroidal anti-inflammatory drug, is prescribed to relieve postoperative and/or chronic joint pain. However, its oral administration often results in serious gastrointestinal adverse effects including duodenal ulceration. Thus, a novel cationic nanoparticle (NP) was explored to minimize the systemic exposure and increase the retention time of PRX in the joint after intra-articular (IA) injection, by forming micrometer-sized electrostatic clusters with endogenous hyaluronic acid (HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
(35 reference statements)
2
15
0
Order By: Relevance
“…Positively charged drug-carriers showed faster penetration and higher uptake than their neutral same-sized counterpart (Bajpayee et al., 2014 ). It is also reported that cationic polymeric nanoparticles had increased retention time and prolonged release profile in joints after IA injection, by forming electrostatic clusters with endogenous hyaluronic acid (Morgen et al., 2013 ; Kim et al., 2016 ). As previously reported, pendant amino groups (–NH 2 ) could increase the cationic nature of polyurethane (Fang et al., 2014 ), we speculated that the amino groups could promote electrostatic interactions with anionic proteoglycans and provide longer retention in cartilage matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Positively charged drug-carriers showed faster penetration and higher uptake than their neutral same-sized counterpart (Bajpayee et al., 2014 ). It is also reported that cationic polymeric nanoparticles had increased retention time and prolonged release profile in joints after IA injection, by forming electrostatic clusters with endogenous hyaluronic acid (Morgen et al., 2013 ; Kim et al., 2016 ). As previously reported, pendant amino groups (–NH 2 ) could increase the cationic nature of polyurethane (Fang et al., 2014 ), we speculated that the amino groups could promote electrostatic interactions with anionic proteoglycans and provide longer retention in cartilage matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Several different classes of drug delivery systems have been studied for intra‐articular use including hydrogels, nanoparticles, and crystalline drug formations . Although each of these systems has different structures and properties, they are all designed to release the drug over prolonged periods after injection into the joint without adverse reactions of the joint tissue to the delivery platform.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The intra-articular injection of the drug using a delivery system can potentially lead to a higher delivered dose while minimizing the side effects to off-target tissues by reducing systemic drug levels. 7 Several different classes of drug delivery systems have been studied for intra-articular use including hydrogels, 8 nanoparticles, 9,10 and crystalline drug formations. 11 Although each of these systems has different structures and properties, they are all designed to release the drug over prolonged periods after injection into the joint without adverse reactions of the joint tissue to the delivery platform.…”
Section: Introductionmentioning
confidence: 99%
“…This non-biodegradable, water insoluble and positively-charged polymer is often used to prepare sustained-release formulations adapted to oral routes. Nanotechnology takes has taken advantage of ERL’s bioadhesive properties in the proposed drug delivery systems for oral [ 22 , 23 ], ocular [ 24 ] and intraarticular [ 25 ] administration. Owing to the above-mentioned properties, ERL is a promising material for preparing nanocarriers for oral delivery of curcumin.…”
Section: Introductionmentioning
confidence: 99%